The complexity of situated text design: a negotiation between standardization and spoken language in a manufacturing company - Carlsson, Anna-Lena; Svensson Harari, Natalia (Frontiers in Communication, 2023)
In information design textbooks, text design is mostly understood as typography and layout. The meaning-making process of language, involving social interaction that affects language, is rarely acknowledged. Instead, texts are supposed to be "clearly" written. We argue that the understanding of text design could benefit from also addressing text production and use situated amid social activity. This article presents a study on a text design process partly based on spoken language and owned by the assembly operators in a workplace. Securing in text sheets the best practice of the smallest entity of the manual assembly tasks-the minima of working-is crucial for the manufacturing industry, but involves capturing the talk and giving the instructive texts a character of transcripts. Our aim within the information design field is twofold: To underline the meaning-making process in language as a social phenomenon and to show that the situated design perspective, i.e., an outlook that admits to the uniqueness of the setting, can also be important for the production and use of certain texts, e.g., instructions, but also affect the language. We asked ourselves: What are the consequences for information design's idea of text design, when meaning-making in language is understood as social and situated in activity? We have studied a design process, and we used observations, interviews, and a text analysis for gathering data. The result shows that the workers' ownership of text documents is crucial for the texts' use, yet the texts used are not living up to the standard of information design textbooks. Also, the text design is a continuous and non-linear collective negotiation between, on the one hand, standardization in language and work procedures, and on the other hand, the capturing of operators' improvements in language.